Curriculum foundations for an integrated, value-based curriculum: The thoughts of Rosnani Hashim - Salem, Abdel Maksoud; Hussien, Suhailah (Bangladesh Institute of Islamic Thought (BIIT), 2016)
This study examines the works of Rosnani Hashim, a Muslim educationalist from Malaysia, in an attempt to draw a framework that constitutes curriculum foundations for a value-based curriculum. Based on the researchers’ review, they found that Hashim’s contribution to curriculum development is significant because she brings together curriculum foundations and curriculum components, as will be seen in the work that will be examined. This study adopted an inductive and analytical methodology based on Hashim’s work—her ideas on curriculum foundations, i.e. belief, worldview, and philosophy of education, and how these are connected to the components of curriculum, namely the learner, the learning experiences, content knowledge and evaluation. In addition, this study compares Hashim’s value-based curriculum model which is a value-based approach against John Dewey’s thoughts. Hashim’s model is a natural progression of international models of curriculum development. What is the unique about her approach is the integrative nature which should be of interest to curriculum developers